The impact of multi-acquiring in the payment system: Evidence from Uruguayan financial inclusion program - Néstor Gandelman; Flavia Roldán; Sofía Viera (Inter-American Development Bank (IDB), 2025)
This paper examines the transition from exclusive card network-acquirer relationships to a multi-acquiring model. Using the case of Uruguay's adoption of multi-acquiring in 2022, as part of a broader financial inclusion program, we document significant market dynamics, including restructured relationships among incumbents and new market entrants. Our analysis, leveraging the Herfindahl-Hirschman Index, reveals decreased market concentration across all payment segments. While fee reductions were initially driven by a government-sponsored price agreement, the increased competition fostered by multi-acquiring stabilized these rates even after the agreement was no longer in effect. Large merchants benefited from enhanced efficiency, but small merchants faced adaptation challenges. These findings underscore the complexities of regulating two-sided payment markets and emphasize the need for balanced interventions to ensure a competitive payment ecosystem.
Keywords: G21; L51; G28; L11; 330; Multi-acquiring; Payment systems; Financial inclusion; Competition; Uruguay